Behind the curtain: unveiling DIS3L2 role in NMD and human cancer - Costa, Paulo (2017)
Nonsense-mediated mRNA decay (NMD) is a surveillance mechanism that targets and degrades mRNAs carrying premature translation-termination codons (PTCs), preventing the production of truncated proteins potentially harmful for the cells. In addition to this, several studies have shown that NMD regulates the levels of many physiological mRNAs that encode full-length proteins. Nevertheless, NMD is inhibited in tumor microenvironment and (de)regulates oncogenes and tumor suppressors in several types of cancer. In humans, the mRNA degradation pathways involve exonuclease proteins, such as the DIS3-like protein family (DIS3, DIS3L1 and DIS3L2); however, it is not known whether these proteins are involved in NMD. In order to unveil the role of DIS3L2 in NMD, we performed its knockdown, by RNA interference, in HeLa cells and measured, by RT-qPCR, the mRNA levels and half-lives of various natural NMD targets. Our results show that some NMD targets are highly stabilized in DIS3L2-depleted cells. In addition, mRNA half-life analysis indicate that these NMD targets are in fact direct DIS3L2 substrates. By performing DIS3L2, TUT4 and TUT7 triple knockdown, we also observed that DIS3L2-mediated decay depends on the terminal uridylyl transferases (TUTases) Zcchc6/11 (TUT7/4) activity. Among the NMD targets regulated by DIS3L2, we highlight GADD45A. GADD45A is involved in cell cycle arrest, DNA damage response and apoptotic process. Furthermore, GADD45A deregulation is associated with several types of cancer, such as, esophageal, lung, bladder and pancreatic. Together, our findings establish the role of DIS3L2 and uridylation in NMD and in the regulation of oncogenes and tumor suppressor gene expression. These results might be highly relevant for the advance in diagnosis, prognosis and treatment of many human cancers.